Role of mathematical models in professional training (Revista de Investigaciones Universidad del Quindío, 2022)
One of the types of scientific models that is used in applied sciences and technology to express propositions through equations, functions, mathematical formulas of a phenomenon and stablish the relationship between two or more unknowns, is the mathematical model. This in turn helps to predict the value of the variables and evaluate their effects according to certain objectives. The proposal that is presented responds to the result of an investigation and exposes the analysis carried out about the types of mathematical models and which are the most relevant to use, so that they contribute to the decision-making process of a situation, and has as the objective is to exchange criteria on the role they play in the professional training of careers students to validate and interpret the information of the original phenomenon so that predictions and conclusions of the process can be made.
Keywords: mathematical models; classification; decision making; professional training